PENGARUH PENERAPAN METODE TALKING STICK TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NU BULULAWANG - Fatmawati Dara Fatona, Siti Muawanatul Hasanah (JIPI (Jurnal Ilmiah Pendidikan Islam), 2023)
The purpose of this study was to determine the process of applying the talking stick method and the effect of student learning outcomes on Islamic Religious Education subjects at SMP NU Bululawang. This research method is a quantitative approach to the type of experiment. data analysis in this study is a type of parametric statistics with the aim of testing the hypothesis t-test. As for the results of the Independent T-Test analysis, a significance value of 0,000 was obtained with an α level of 5% which means Ho was rejected and Ha was accepted, so the results of the study concluded that the application of the talking stick method proved to have a good effect on student learning outcomes in Islamic Religious Education subjects.